A Case Study of Marma Chikitsa in Tennis Elbow - Singh, Shailesh; Sharma, Purushottam Das; Sharma, Shri Ram; Sharma, Dinesh Kumar; Deepa (International Research Journal of Ayurveda & Yoga, 2024)
Tennis elbow is a painful condition and causes restricted movement of forearm which requires treatment for long period. Till date only symptomatic treatments are available in modern science like use of anti-inflammatory, analgesic drugs, steroids injection, physiotherapy, exercise etc. But none of these provide satisfactory permanent result. Long term use of modern treatment causes adverse effects. Usually, ‘wait-and-watch policy’ of treatment guideline is recommended in most of medical texts. This guideline made it worsen day by day. According to Ayurveda, Snayugata vata can be correlated with the condition of tennis elbow. In the field of Marma Chikitsa, this condition can be treated without oral use of any chemical compound which helps the individual to prevent adverse effect of modern medicine. Hence, in this study a case of tennis elbow (Snayugata vata) was treated by Marma Chikitsa for a period of 15 days. This therapy provided considerable relief in pain and movement of the elbow joint.